Penguatan Pemahaman Sejarah Lokal melalui Eksplorasi Situs Sejarah Kota Tual bagi Siswa SMK Negeri 3 Ohoinol - Jacomina Selfisina; Efilina Kissiya; Jenny K. Matitaputty; Pithein Montouw; Altrigita Parewang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The utilization of local history as a learning resource remains limited in history education, resulting in students having insufficient understanding of their regional historical heritage. In fact, local historical sites can serve as contextual learning resources that enhance students’ historical understanding and awareness. This community service activity aimed to strengthen students’ understanding of local history through the exploration of historical sites in Tual City. The program was conducted at SMK Negeri 3 Ohoinol and involved 52 students from grades XI and XII. The implementation methods included local history socialization, educational video screenings, interactive discussions, and field visits to several historical sites in Tual City, including Nen Dit Sak Mas, Kerbau Siuw, Watraan Japanese Fort, Duroa Fort, and historical cannons. The activities were carried out over two days using a contextual learning approach that connected historical materials with students’ real-life environment. The results indicated an improvement in students’ understanding of local history, reflected in their active participation during discussions, their ability to explain historical information gained from the activities, and their increased interest in local historical and cultural heritage. Furthermore, the program fostered students’ awareness of the importance of preserving historical sites as part of the cultural identity of the local community. Therefore, the exploration of historical sites can serve as an effective contextual learning strategy to strengthen local historical understanding among students.